2005
DOI: 10.1002/ijc.21189
|View full text |Cite
|
Sign up to set email alerts
|

SCCA antigen combined with alpha‐fetoprotein as serologic markers of HCC

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer in the world. Because of its increased incidence in the last decade and the estimated further increase in the next 2 decades, HCC is arousing great interest. In Europe and North America, it commonly develops on cirrhotic livers, and surveillance programs have therefore been suggested to identify early HCC, at a stage when it remains suitable for surgical therapy and has a better clinical outcome. The only serologic marker used in clinical practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 16 publications
(21 reference statements)
4
38
2
Order By: Relevance
“…This property is useful in the early detection and followup diagnoses for patients treated for HCC [51] . At a threshold of 0.368 ng/mL, SCCA has an AUC of 0.705, a sensitivity of 84.2% and a specificity of 48.9% [52] .…”
Section: Squamous Cell Carcinoma Antigenmentioning
confidence: 99%
“…This property is useful in the early detection and followup diagnoses for patients treated for HCC [51] . At a threshold of 0.368 ng/mL, SCCA has an AUC of 0.705, a sensitivity of 84.2% and a specificity of 48.9% [52] .…”
Section: Squamous Cell Carcinoma Antigenmentioning
confidence: 99%
“…Their usefulness does not vary by country or HCC etiology. In addition to the HCC tumor markers reviewed here (AFP, AFP-L3, and DCP), many serum biomarkers, including glypican-3, insulin-like growth factor, osteopontin, golgi protein-73, and squamous cellular carcinoma antigen, have been investigated as candidates for HCC tumor markers [60][61][62][63][64][65][66]. These novel potential HCC tumor markers, alone or in combination with other markers, will further contribute to the management of patients with HCC.…”
Section: Perspectivementioning
confidence: 99%
“…The Cox multivariate analysis of another study demonstrated that SCCA-IgM levels (P= 0.004) was an independent predictor of survival and, combining SCCA-IgM with AFP, the sensitivity reached 94% (13). Another study also reported that the combination of AFP and SCCA yielded a correct serological diagnosis in 90.83% of HCC patients, indicating that combining the two markers may achieve a higher sensitivity (17).…”
Section: Discussionmentioning
confidence: 87%
“…1 The sample size ranged between 81 and 961. Five studies were performed in Asian (14,(20)(21)(22)(23), 5 in European (7,13,15,17,18) and 2 in African populations (16,19).…”
Section: Resultsmentioning
confidence: 99%